Artificial Intelligence and Islamic Finance: Enhancing Sharia Compliance and Social Impact in Banking 4.0 - Zohaib Sain; Hendri Hermawan Adinugraha (Journal of Business Management and Islamic Banking, 2025)
Research Aims: This research explores consumers’ perspectives on adopting artificial intelligence (AI) in Asian countries, focusing on its role in the banking sector. Methodology: This quantitative research has distributed questionnaires to eleven Asian countries: Pakistan, China, Iran, Saudi Arabia, Indonesia, Malaysia, Bangladesh, Nepal, India, Afghanistan, and Thailand. The study received 550 usable responses, which provided valuable insights into consumer attitudes towards AI in banking. Research Findings:The findings revealed that several factors, including responsiveness, perception of AI, individual perspective, perceived value, and comprehension of AI technology, significantly and positively impact AI adoption plans in the banking sector. However, risk perception exhibited a negative yet considerable relationship with adoption intentions. Theoretical Contribution: This research is unique because it provides a better understanding of consumer perceptions of AI adoption in the banking sector in Asian countries. It offers a unique perspective on the strategic implications for banking management in leveraging AI technology for improved customer service and revenue generation, with a specific focus on the growing relevance of AI in Islamic finance. Research limitation and implication: These implications are essential for strategic decision-making in the banking industry. The findings highlight the importance of building consumer trust and confidence in digital technology, enabling banks to overcome risks and enhance customer satisfaction. For Islamic financial institutions, these insights can guide the integration of AI in ways that align with Sharia principles, such as ensuring transparency, ethical data use, and risk-sharing mechanisms. This will not only improve operational efficiency but also strengthen the appeal of Islamic banking to tech-savvy consumers.